Effect of dual phase structure induced by chemical segregation on hot tearing reduction in additive manufacturing - Guo, Chaoyang (2023)
It is of great significance to explore the chemical compositions, which have not been hitherto examined for their suitability for additive manufacturing (AM), so as to broaden AM's material library. Since solidification cracking is a major impediment in AM of alloys, especially high entropy alloys (HEAs), a detailed study on the cracking issue during AM is imperative. Keeping this in mind, a customized laser powder bed fusion (LPBF) setup is utilized to fabricate a compositionally graded AlxCoCrFeNi (x = 0.04–0.75) HEA, using the equiatomic AlCoCrFeNi and CoCrFeNi powders as feedstock, to examine the compositional range that enables crack-free fabrication. Experimental results show that when x ≤ 0.7, crack-free fabrication is possible. This compositional range exceeds the threshold reported in the recent literature. Microstructural characterization reveals a constant dual phase structure throughout the gradient, which is induced by the chemical segregation. Further analysis shows that both utilizing AlCoCrFeNi powder as Al source and the segregation contribute to the enhanced printability. The results suggest that the dual phase structure introduced by chemical segregation can effectively inhibit the initiation and propagation of hot tearing problem in metal additive manufacturing.